Treatment of pertrochanteric fractures in elderly patients: is dynamic fixation so important? - Ivan M. Shcherbakov (Russian Ilizarov Scientific Center for Restorative Traumatology and Orthopaedics, 2021)
Abstract. Introduction The problem of complications after surgical treatment of pertrochanteric fractures in elderly patients is relevant and far from a solution. Materials and methods The retrospective study was based on the analysis of the results of treatment of 129 patients with pertrochanteric femoral fractures (average age 76 years). All fractures in the early time from trauma were fixed with two types of cephalomedullary nails, either dynamic or static. All patients could not limit the load on the operated limb after surgery because of different reasons. Results The results of treatment were evaluated in 109 patients after one year. In dynamic cephalomedullary fixator group (59 patients), there were 7 orthopedic complications with a functional Harris scale result of 68 points (range, 26 to 94 points). In static cephalomedullary fixator group (50 patients), there were 14 orthopedic complications with a functional Harris score of 56.5 points (range, 15 to 92 points). Discussion Higher results of treatment in the group of dynamic fixator in the condition of full-weight bearing on the operated limb may be associated with the possibility of dynamization of the part of fixator in response to bone resorption in the contact area of bone fragments. The use of dynamic cephalomedullary fixators instead of static ones for treatment of pertrochanteric femoral fractures in elderly patients exercising full weight-bearing leads to a decrease in orthopedic complications (from 28 to 11.9 %) and improves the functional results of treatment.